Sujeito e tópico do discurso - Pontes, Eunice (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
In this article, part of a more extensive work on subjects (forthcoming), I discuss the usually made claim that subjects are topics; I examine the relation between sentence topic and discourse topic, following Van Dijk and others; and I show the need to distinguish sentence topic from discourse topic and propose to call the latter 'theme'. Some of Givón's ideas about this subject are presented and discussed. The idea that left dislocation is a device for reintroducing a topic is examined and confronted with Portuguese data. Finally, I show how the subject of a  sentence express the teme of a text. The objects, on the other hand, are not necessarily linked with the theme of the text.